A Review on the Use of Confocal Laser Endomicroscopy in the Bile Duct. (19th April 2012) - Smith, Ioana; Kline, Pamela E.; Gaidhane, Monica; Kahaleh, Michel
Abstract : Background . Current methods to diagnose malignant biliary strictures are of low sensitivity. Probe-based confocal laser endomicroscopy (pCLE) is a new approach that can be used to evaluate in vivo histopathology of the GI tract. This paper is of studies evidencing pCLE's application in the diagnosis of indeterminate biliary strictures. Methods . This paper examined peer-reviewed studies conducted between January 2000 and November 2011. A PubMed search for relevant articles was performed using the following keywords:"pCLE", "confocal", "endomicroscopy", "probe-based confocal laser endomicroscopy", "and "bile duct". Further individual review was done to assess the screened articles' relevance to the topic. Results . After individual review, 6 studies were included; with a cumulative sample size of 165, with 75 subjects identified as having a malignancy. These studies included tertiary care centers in Germany, France, and USA, including one multicenter trial. 3 studies assessed pCLE's specificity (range 67%–88%), sensitivity (range 83%–98), and accuracy (range 81%–86%). Conclusion . Confocal endomicroscopy is a novel and promising modality for the biliary tree. Further studies need to be conducted both to establish its usefulness for the diagnosis of indeterminate biliary strictures and to understand the histological meaning of the imaging patterns that are observed.